INTEGRATING ISLAMIC RELIGIOUS EDUCATION AND SOCIAL EMOTIONAL LEARNING FOR DEVELOPING MODERATE CHARACTER IN STUDENTS - Rohman, M. Abdul; Muhibbi, Moh. Saddad; Mafrukha, Wahyu Nisawati; Suratin, Sonia Isna (Sekolah Tinggi Agama Islam Al Hidayah, 2025)
Background: The increasingly complex socio-religious dynamics and the increasing vulnerability to extremism demand innovation in Islamic Religious Education (PAI) learning that is able to strengthen religious moderation and inclusive character of students. The integration of Social Emotional Learning (SEL) is considered relevant to address these challenges. Purpose of the Study: This study aims to develop and analyze an Islamic Religious Education (PAI) learning model based on the integration of Islamic values ​​and Social Emotional Learning competencies in strengthening students' moderate character. Methods: The study used a qualitative approach through literature study with systematic analysis of relevant academic sources to obtain a comprehensive conceptual understanding. Results: The findings indicate that the integration of PAI-SEL is effective in strengthening religious moderation through the development of self-awareness, empathy, emotional regulation, and ethical decision-making. This model supports the internalization of the values ​​of national commitment, tolerance, anti-violence, and respect for local culture through reflective and contextual learning. Conclusions: The integration of PAI and Social Emotional Learning is an applicable and relevant pedagogical strategy for the development of the PAI curriculum, especially in shaping the moderate character of students who are adaptive to the challenges of a pluralistic society towards Golden Indonesia 2045.